Implementing The Independent Curriculum in Physical Education at Public Senior High School 5 of Bungo - Setiawan, Danu; Saputra, Deka Ismi Mori; Pilitan, Raja Bani (FKIP Universitas Wisnuwardhana, 2026)
This study addresses the limited implementation of student-centered learning in Physical Education at Public Senior High School 5 of Bungo, where conventional lecture-based approaches still dominate. Teachers’ limited understanding of the Independent Curriculum, particularly in student-centered learning, differentiated instruction, and formative assessment, has resulted in low student participation and motivation. This research aims to analyze the implementation of the Independent Curriculum in Physical Education and identify its supporting and inhibiting factors. A qualitative descriptive approach was employed. The study was conducted at Public Senior High School 5 of Bungo involving the principal, Physical Education teachers, and students as research subjects. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the implementation of the Independent Curriculum had been carried out effectively through student-centered, differentiated, and project-based learning. Teachers adapted teaching modules and learning activities based on students’ needs and abilities. As a result, students became more active, motivated, and engaged. Supporting factors included teacher readiness, school support, and student enthusiasm, while obstacles involved limited facilities and difficulties in designing project-based learning. In conclusion, the Independent Curriculum improves the quality of Physical Education learning, although continuous improvement is needed to overcome existing challenges.